AN EXTENDED REVIEW AND SUMMARY ON FACTS ABOUT ETIOLOGY EPIDEMIOLOGY CLINICAL DIAGNOSIS AND MANAGEMENT OF SCRUB TYPHUS INFECTION - Nagaraju, G. V.; Pavan Kumar, G. V. (Asian Journal of Pharmaceutical Research and Development, 2018)
Scrub typhus is also known as bus typhus inaction and it is a serious public health problem in the Asia-Pacific area. It threatens one billion peoples are effected worldwide, and causes illness in one million people for an each year. Caused by Orientia tsutsugamushi, scrub typhus can result in severe multi organ failure with a case fatality rate up to 70% without appropriate treatment. The antigenic heterogeneity of O. Tsutsugamushi precludes generic immunity and to the allows reinjection. As it is a neglected disease, there is still a large gap in our knowledge of the disease, as evidence by the sporadic epidemiologic data and others relating to the public health information regarding scrub typhus in its endemic areas. It is a gram-negative bacterium, this infection can be perfectly treated with the specific antibiotics. Early treatment gives best results those who are infected with this infection it gives better therapeutic outcomes. Oral medication is effective for mild cases, but the parenteral route is often necessary for severely ill patients. Similar to treatment for other rickettsial diseases, doxycycline is one of most effective antibiotics for treating scrub typhus infection. Key Words: Scrub typhus, threatens one billion peoples, gram-negative bacterium, Oral medication.